2005
DOI: 10.1016/j.jaridenv.2005.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Landsat monitoring of playa-lakes in the Spanish Monegros desert

Abstract: Small playa-lakes in Monegros, Spain, are high-value habitats for endemisms, threatened by landscape transformations and development of newly irrigated lands. The purpose of monitoring these fragile habitats is to detect their future disturbance, i.e. the effects of changing their natural hydrological regime, such as increasing their flooding surface area and habitat degradation by fresh and polluted water flow inputs. Landsat imagery is used for this purpose, facing the lack of regular ground data about their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 32 publications
(27 reference statements)
0
48
0
1
Order By: Relevance
“…Satellite images have been used to map large permanent wetlands [see 14 for a review] and, occasionally, to reconstruct their temporal dynamics over the past decades [15][16][17]. However, its application on seasonally flooded systems has been scarce [18][19][20][21], and, in particular, for small-sized wetlands [22] due to the difficulty of identifying waterbodies if below pixel size, e.g., [23]. High spatial resolution remote sensing may be an alternative for the delineation of small-sized wetlands.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite images have been used to map large permanent wetlands [see 14 for a review] and, occasionally, to reconstruct their temporal dynamics over the past decades [15][16][17]. However, its application on seasonally flooded systems has been scarce [18][19][20][21], and, in particular, for small-sized wetlands [22] due to the difficulty of identifying waterbodies if below pixel size, e.g., [23]. High spatial resolution remote sensing may be an alternative for the delineation of small-sized wetlands.…”
Section: Introductionmentioning
confidence: 99%
“…ISODATA used in this study is an unsupervised method for image processing, and the detailed information on a target land cover is not needed for classification. For this reason, ISODATA has frequently been used in waterbody classification [42,43]. However, unsupervised methods are limited by spectrally homogeneous groupings identified by the classification process.…”
Section: Some Issues With Image Processingmentioning
confidence: 99%
“…As a common feature of internal drainage basins, playas are vital for understanding the natural habitats of endemic microbes, plants and animals [1] and for interpreting the interrelation between climate and tectonic activity within continents [2]. Studies also proved that playas sediments could be potential hydrocarbon reservoirs [3], as they may contain significant numbers of thin fluvial sheetflood deposits.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have suggested that a framework for surface sedimentary facies or depositional environments is needed in playas [4][5][6][7]. Over the past decades, a number of studies have applied remote sensing techniques to study playas and have demonstrated the usefulness of remote sensing in such studies (e.g., [1,2,[8][9][10][11][12][13][14][15]). However, most of these studies have focused on mapping evaporite minerals and water bodies.…”
Section: Introductionmentioning
confidence: 99%